Asymmetries of the balanced SSFP profile. Part II: white matter. - Miller, K; Smith, S; Jezzard, P (2010)
The signal profile measured in balanced steady-state free precession has been shown to exhibit tissue-dependent asymmetries that were hypothesized to relate to properties of the tissue microenvironment. It was proposed that balanced steady-state free precession asymmetry may reflect subtle features of the frequency distribution in tissue. The present work investigates the large balanced steady-state free precession asymmetries observed in white matter. First, maps quantifying the asymmetry are presented, which demonstrate considerable heterogeneity within white matter, with some tracts exhibiting significant asymmetry and others having a nearly symmetric profile. These maps are compared with a diffusion-tensor atlas and indicate that the highest asymmetry is found in tracts oriented perpendicular to the main magnetic field. Measurements conducted at multiple repetition times suggest that the asymmetries are characterized by relatively small frequency shifts. These results are discussed in the context of previous work studying gradient-recalled echo (GRE) signal behavior in white matter, and it is suggested that these two techniques are detecting closely related phenomena.